Research priorities in the administration of public education in The Kingdom of Saudi Arabia - Alsalem, Manal Abdulaziz; Aljuwayid, Mashael Saleh; Alghurayr, Mashael Mohammed (Journal of Educational and Psychological Sciences, 2023)
The study aimed at identifying research priorities in Public Schools Administration in Saudi Arabia, in the areas: school administration; educational supervision; professional development of educational employees; public schools financing; public schools administrative processes, employing technology in educational administration processes; and educational and psychological aspects of educational administration. The study adopted the methodology of future studies using the Delphi method and two tours were conducted by a group of experts working in public schools in different administrative levels: schools, supervision offices, education departments, and the Ministry of Education. In the first tour, their number reached (28) experts; while in the second tour (25) experts.The study concluded that all areas of public education surveyed in this study were of high research priority. Moreover, the results of the study revealed that the area which occupied the highest priority was the area of ‘employing technology in educational administration processes’. The study identified the sub-topics related to each of the seven areas investigated in the study, which were determined as a research priority. and recommended that the employees of educational administration departments in the Saudi universities should benefit in their researches from the list of research priorities which this study came out with.
Keywords: Research priorities; public education; educational administration; Delphi method